PEMBENTUKKAN KARAKTER SISWA MELALUI KEGIATAN PEMBELAJARAN AKIDAH AKHLAK DI MTS EL JASMEEN SINGOSARI KABUPATEN MALANG - Vivi Irma; Azhar Haq; Adi sudrajat (Vicratina : Jurnal Ilmiah Keagamaan, 2020)
Character formation is one of the supporting factors of an effort that can change the character of students who were previously bad to good. The results of the observation of researchers at Mts El Jasmeen Singosari, that there are some students who are less active, lack of morals to teachers, lack of confidence, and undisciplined time especially in the subjects of the Akidah Akhlak.maka very clearly in the study of the moral creed as a whole pay attention to the behavior that appears in schools and in the community. Because with the emergence of behavioral violations that make a negative impact can be done by school children. So in this study will examine the moral code. Because in moral learning there are materials that can deliver the character of a child to be noble. The researcher conducts research related to how the moral teacher in planning learning activities in shaping student character, how the moral teacher strategy in shaping student character, and what are the solutions given by the moral teacher to overcome the obstacles in character building through moral learning. Researchers used a descriptive qualitative approach. Data collection techniques using interviews, observation, and documentation. in its application the teacher has ways to overcome the problem by forming these characters. and will be explained in the information below.